2017
DOI: 10.2174/1874434601711010263
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Obtaining Informed Consent in Emergency Ward: A Qualitative Study in One Iranian Hospital

Abstract: Background and Objective:Regarding the fact that emergency ward has unique characteristics, whose uniqueness affects informed consent processes by creating specific challenges. Hence, it seems necessary to identify the process and challenges of informed consent in the emergency ward through a qualitative study to understand actual patients’ and health care providers’ experiences, beliefs, values, and feelings about the informed consent in the emergency ward. Through such studies, new insight can be gained on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Examples of factors include assisting a physician who believes the nurse is not suitably experienced or qualified to provide health care, taking therapeutic measures to delay patient death, conducting unnecessary treatments and tests, ignoring errors made by other health care providers, working with inexperienced health care providers, 38 and obtaining informed consent. 39 The recent study has indicated that environmental barriers to observing professional ethics in the emergency department are high, which is consistent with the results of the current study. 19 Currently, we are in the middle of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Examples of factors include assisting a physician who believes the nurse is not suitably experienced or qualified to provide health care, taking therapeutic measures to delay patient death, conducting unnecessary treatments and tests, ignoring errors made by other health care providers, working with inexperienced health care providers, 38 and obtaining informed consent. 39 The recent study has indicated that environmental barriers to observing professional ethics in the emergency department are high, which is consistent with the results of the current study. 19 Currently, we are in the middle of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 18 articles that were reviewed, 5 studies were literature reviews and systematic reviews, 14 16 , 28 , 34 4 were cross-sectional studies, 22 , 25 , 31 , 32 2 were qualitative studies, 21 , 31 3 were ethical articles, 24 , 27 , 30 2 were cohort/case-control studies, 26 , 29 and 2 were review articles. 23 , 33 The themes explored in these studies were emergency consent, ethical and theoretical concepts of informed consent, stakeholders’ perceptions to informed consent, challenges of emergency surgery consent, and policies on emergency surgery consent.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have argued that paternalism is justified for illiterate people because they lack information and understanding and therefore are unable to make informed decisions [ 20 , 21 ]. Davoudi et al described medical paternalism as a cultural belief that the patients and their attendants do not have the required literacy to make decisions especially when they are anxious like in an emergency setting [ 22 ]. Other research has shown the paternalistic relationship patients have with their doctors especially in emergencies [ 13 ] which might be heightened in patients with a lower level of education.…”
Section: Discussionmentioning
confidence: 99%